Development of a secondary school-based digital behaviour change intervention to improve tooth brushing - Zoe Marshman; Sarab El-Yousfi; Ian Kellar; Donna Dey; Mark Robertson; Peter Day; Ivor Chestnutt; Sue Pavitt; Mariana de Araujo; Nicola Innes (BMC, 2021)
Abstract Background Dental caries in adolescents remains a significant public health problem with few oral health promotion interventions aimed at reducing dental caries in secondary school-aged students. Previous oral health and mobile health (mHealth) research has suggested the need for the development of a school-based behaviour change intervention incorporating a digital component. This study aimed to describe the development process of a behaviour change intervention to improve the oral health of students aged 11-16 years attending secondary schools in the UK. Methods A six-step process was used to develop the complex intervention informed by behaviour change theory and involving students, young people, parents and teachers in the process. The steps were: (1) identifying the target behaviours, namely tooth brushing with a fluoride toothpaste (2) identifying the theoretical basis and developing the causal model (3) reviewing the relevant literature and developing the logic model (4) designing the intervention with young people, parents and school staff (5) specifying the intervention content and (6) translating this content into features of the intervention and piloting. Results The resultant intervention included a quality-assured classroom-based session (CBS) (guided by a lesson plan and teaching resources), delivered by school teachers which was embedded within the school curriculum. This CBS was followed by a series of (Short Message Service) SMS texts delivered twice daily to student's mobile telephones with the content, duration and timing of the messages informed by involvement of students and young people. Conclusions An intervention to improve the oral health of secondary school students through improved tooth brushing was rigorously developed based on behaviour change theory and work with young people, parents and school staff. Further research is needed to evaluate the outcomes and processes involved following the delivery of this intervention. BRIGHT Trial Trial Registration ISRCTN12139369.